ECONOMICS OF RICE MARKETING IN SOUTHERN AGRICULTURAL ZONE OF PLATEAU STATE, NIGERIA - Nansel, N.; Abdullahi, I. M.; Sani, R. M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the economics of rice marketing in the Southern Agricultural Zone of Plateau State, Nigeria. A multistage sampling technique was employed to selecting 222 rice marketers from the study area. Primary data were collected using structured questionnaires and interviews. Data were analyzed using descriptive statistics, Shepherd’s Index, Acharya’s approach and multiple regression analysis. The results showed that 63.96% of respondents were male, with the majority (48.65%) aged between 31–45 years. Majority (69.82%) were married, while 43.69% had secondary education. Most respondents had 6–10 years of marketing experience (41.89%) and the majority operated on a small scale (45.95%). Profitability analysis revealed an average monthly revenue of ₦385,000.00, with a total cost of ₦342,500.00, resulting in a net monthly profit of ₦42,500.00. Marketing efficiency measured using Shepherd’s Index (1.12) indicated moderate efficiency, while Acharya’s Marketing Margin (23.5%) showed a fair profit margin. Regression results indicated that variables such as transportation cost (p < 0.01), storage cost (p < 0.01), access to credit (p < 0.01) and market access (p < 0.05) significantly influenced profitability. The model had an R² of 0.618, implying that 61.8% of the variation in profitability was explained by the variables considered. The major constraints faced by marketers were price instability (75.68%), inadequate credit access (66.22%), high transportation costs (62.16%) and poor storage facilities (59.46%). The study concluded that rice marketing in the Southern Agricultural Zone of Plateau State is profitable but constrained by infrastructural, financial and institutional challenges. It is recommended that government and stakeholders should stabilize rice prices, improve storage facilities, enhance access to affordable credit and rehabilitate rural road networks to boost marketing efficiency and profitability.